Left bundle branch block causes left atrial dyssynchrony: a result of atrio-ventricular mechanical interaction. (14th October 2021) - Hammersboen, L E R; Stugaard, M; Remme, E W; Donal, E; Duchenne, J; Voigt, J U; Galli, E; Sletten, O J; Aalen, J; Smiseth, O A
Abstract: Introduction: Left bundle brach block (LBBB) leads to left ventricular (LV) mechanical dyssynchrony with septal flash and delayed lateral wall contractions. Since atrium and ventricle are anatomically connected, dyssynchronous LV contractions may be transmitted to the left atrium, thereby disturbing left (LA) function. Purpose: To test the hypothesis that patients with LBBB have LA dyssynchrony induced by tethering to the dyssynchronous left ventricle. Methods: Myocardial strain was measured by speckle-tracking echocardiography in 20 non-ischaemic heart failure patients with LBBB, before and 6 months after cardiac resynchronization therapy (CRT), and in 20 healthy controls. For the LA, dyssynchrony was measured as time delay between onset of the interatrial septum and the lateral wall, and for the LV, between onset septal flash and onset lateral wall contraction. White arrows in Figure indicate onset LA stretch. Results: As shown in the Figure, patients with LBBB and HF had marked LA reservoir phase dyssynchrony. Before CRT time delay from onset LA septal stretch to onset lateral wall stretch was 125±71 ms (mean±SD), and decreased to 23±70 (p<0.0001) with CRT. In controls there was a small delay of 34±56 ms. The LA dyssynchrony correlated with LV dyssynchrony (r=0.50, p=0.033), supporting the hypothesis that LA dyssynchrony in LBBB represents mechanical interaction due to tethering between the respective walls. Conclusions: Patients with LBBB had marked LA reservoir phase dyssynchrony, which was abolished with CRT. The LA dyssynchrony was attributed to direct LV-LA mechanical interaction. The observed LA resynchronization by CRT represent an additional benefit of CRT in patients with heart failure. Funding Acknowledgement: Type of funding sources: None.